2006
DOI: 10.1161/01.res.0000252345.80198.97
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Heat Shock Transcription Factor 1 Plays a Critical Role in Adaptive Cardiac Hypertrophy

Abstract: Abstract-Exercise-induced cardiac hypertrophy has been reported to have better prognosis than pressure overloadinduced cardiac hypertrophy. Cardiac hypertrophy induced by exercise was associated with less cardiac fibrosis and better systolic function, suggesting that the adaptive mechanisms may exist in exercise-induced hypertrophy. Here, we showed a critical role of heat shock transcription factor 1 (HSF1), an important transcription factor for heat shock proteins, in the adaptive mechanism of cardiac hypertr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
74
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(79 citation statements)
references
References 57 publications
5
74
0
Order By: Relevance
“…The cardioprotective gene Hsp70 was reported to be upregulated in exercise-induced (physiological) but not in pressure overload-induced (pathological) cardiac hypertrophy. 9 In the present work, Hsp70 protein expression increased in swimming exercise but not in TAC model ( Figure S5D). Hence, we concluded that the present swimming exercise-induced cardiac hypertrophy was physiological.…”
Section: Tac (Day)supporting
confidence: 41%
“…The cardioprotective gene Hsp70 was reported to be upregulated in exercise-induced (physiological) but not in pressure overload-induced (pathological) cardiac hypertrophy. 9 In the present work, Hsp70 protein expression increased in swimming exercise but not in TAC model ( Figure S5D). Hence, we concluded that the present swimming exercise-induced cardiac hypertrophy was physiological.…”
Section: Tac (Day)supporting
confidence: 41%
“…The expression and/or phosphorylation of hsp27 in the heart is increased in response to chronic pressure overload [20], both physiological and pathological hypertrophy [13], heart failure [21,38,39], oxidative stress [24,25], ischemic injury [22], and haemorrhagic shock [23]. Increased hsp27 expression prevents cardiac dysfunction and hypertrophy during chronic pressure overload [13], protects against doxorubicin-induced cardiomyopathy [26,27], and prevents tachypacing-induced atrial remodelling and atrial fibrillation [14,17,16,19]. The ability of heat shock to protect against doxorubicin-induced cardiomyopathy involves an increase in p38 activity and hsp27 phosphorylation [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Hsp27 comprises approximately 0.1% of the total protein content [12] in the adult heart and its expression is increased during both physiological and pathological hypertrophy [13]. This increase is thought to be cardioprotective since the constitutive activation of heat shock transcription factor 1, which leads to an increase in hsp27 expression, prevents cardiac dysfunction and hypertrophy during chronic pressure overload [13].…”
Section: Introductionmentioning
confidence: 99%
“…The adaptation of the heart to long-term regular physical training leads to cardiac morphological changes, including increased left ventricular cavity and wall thickness, (LV) end-diastolic cavity diameter, LV end-systolic Diameter and LV mass, described as athlete's heart (Pluim et al, 2000;Spirito et al, 1994;Pelliccia et al, 1996;Dorn and Force, 2005;Sakamoto et al, 2006;Urhausen and Wilfried, 1999). Cardiac hypertrophy induced by training was associated with better systolic and diastolic function and with less cardiac fibrosis suggesting that the adaptive mechanisms may exist in exercise-induced hypertrophy (Sakamoto et al, 2006;Urhausen and Wilfried, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac hypertrophy induced by training was associated with better systolic and diastolic function and with less cardiac fibrosis suggesting that the adaptive mechanisms may exist in exercise-induced hypertrophy (Sakamoto et al, 2006;Urhausen and Wilfried, 1999). Sport-specific adaptations and differentiation of an athlete's heart were described 100 years ago (Morganroth et al, 1975;Landry et al, 1985;Hoogsteen et al, 2004).…”
Section: Introductionmentioning
confidence: 99%